PDX models recapitulate the genetic and epigenetic landscape of pediatric T‐cell leukemia. Issue 12 (2nd November 2018) - Richter‐Pechańska, Paulina; Kunz, Joachim B; Bornhauser, Beat; von Knebel Doeberitz, Caroline; Rausch, Tobias; Erarslan‐Uysal, Büşra; Assenov, Yassen; Frismantas, Viktoras; Marovca, Blerim; Waszak, Sebastian M; Zimmermann, Martin; Seemann, Julia; et al.
Abstract: We compared 24 primary pediatric T‐cell acute lymphoblastic leukemias (T‐ALL) collected at the time of initial diagnosis and relapse from 12 patients and 24 matched patient‐derived xenografts (PDXs). DNA methylation profile was preserved in PDX mice in 97.5% of the promoters (ρ = 0.99). Similarly, the genome‐wide chromatin accessibility (ATAC‐Seq) was preserved remarkably well (ρ = 0.96). Interestingly, both the ATAC regions, which showed a significant decrease in accessibility in PDXs and the regions hypermethylated in PDXs, were associated with immune response, which might reflect the immune deficiency of the mice and potentially the incomplete interaction between murine cytokines and human receptors. The longitudinal approach of this study allowed an observation that samples collected from patients who developed a type 1 relapse (clonal mutations maintained at relapse) preserved their genomic composition; whereas in patients who developed a type 2 relapse (subset of clonal mutations lost at relapse), the preservation of the leukemia's composition was more variable. In sum, this study underlines the remarkable genomic stability, and for the first time documents the preservation of the epigenomic landscape in T‐ALL‐derived PDX models. Synopsis: Although patient‐derived xenografts (PDXs) of pediatric T‐cell acute lymphoblastic leukemias (T‐ALL) are generally stable at the genomic level, little is known about conservation of their epigenetic features and chromatin architecture. This study investigates epigenomic profiles of T‐ALL PDXs. Pediatric T‐ALL cells largely remain stable in their genomic and epigenomic profile when xenografted into NSG mice. PDXs from patients with type 1 relapse (all clonal mutations maintained at relapse) are more stable than PDXs from patients with type 2 relapse (subset of clonal mutations lost at relapse). PDX models of pediatric T‐ALL largely preserve the DNA methylation and the chromatin accessibility profiles (ATAC‐Seq) of the original leukemias. Hypoaccessible/hypermethylated regions in PDX compared to primary samples are associated with immune response functions, possibly reflecting the immune‐deficiency of the mice and the incomplete interaction between murine cytokines and human receptors. Abstract : Although patient‐derived xenografts (PDXs) of pediatric T‐cell acute lymphoblastic leukemias (T‐ALL) are generally stable at the genomic level, little is known about conservation of their epigenetic features and chromatin architecture. This study investigates epigenomic profiles of T‐ALL PDXs.